Cross-leg flap in a burn patient: our experience from a tertiary center from Northern Tanzania. Issue 10 (11th October 2022) - Lodhia, Jay; Jusabani, Mubashir; Msuya, David
Abstract: Lower limb trauma with significant tissue loss poses a great challenge to the surgeons. Cross-leg flaps were first described in 1854 and are still used for limb-salvage surgeries in those not suitable for free tissue transfer or in resource-limited settings. Herein we present a case of a 16-year-old girl, otherwise well, who sustained burn injury to her right leg while cooking exposing the anterior aspect of her tibia. Limb-salvage surgeries were done including cross-leg 'fascio-cutaneous' flap with positive outcome. Herein, we share our experience showing an impactful and reliable option for limb salvage in resource-limited setting.